2004
DOI: 10.1002/pmic.200400825
|View full text |Cite
|
Sign up to set email alerts
|

Mass spectrometric protein structure characterization reveals cause of migration differences of haptoglobin α chains in two‐dimensional gel electrophoresis

Abstract: Haptoglobin belongs to the major constituents of plasma and acts as hemoglobin-binding and acute-phase protein. Due to the occurrence of three major allelic variants and further structural modifications, the alpha chains of haptoglobin form varying spot patterns in two-dimensional gel electrophoresis (2-DE) gels, which is generally observed in differential proteome analyses using plasma or related body fluids of humans. In the present study plasma samples from 10 donors of initially unknown haptoglobin phenoty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
52
0
6

Year Published

2005
2005
2019
2019

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 42 publications
(65 citation statements)
references
References 34 publications
7
52
0
6
Order By: Relevance
“…However, several biochemical modifications appear to be superimposed on genetic polymorphisms. Using MS protein structure characterization, the cause of migrational differences of haptoglobin a chains in 2-DE was elucidated [35,36]. It was shown that at least three structurally different protein species can be differentiated and accounted for the most commonly observed spot patterns of haptoglobin a chains.…”
Section: Clinical Applications -Biomarker Identificationmentioning
confidence: 99%
“…However, several biochemical modifications appear to be superimposed on genetic polymorphisms. Using MS protein structure characterization, the cause of migrational differences of haptoglobin a chains in 2-DE was elucidated [35,36]. It was shown that at least three structurally different protein species can be differentiated and accounted for the most commonly observed spot patterns of haptoglobin a chains.…”
Section: Clinical Applications -Biomarker Identificationmentioning
confidence: 99%
“…One sample measurement series (M5) was recorded after fractionated precipitation. Protein mixtures were analyzed with a Reflex III MALDI TOF mass spectrometer (Bruker Daltonik) equipped with the SCOUT source and delayed extraction and operated in linear positive ion mode using an acceleration voltage of 20 kV [25]. Spectra were recorded in a mass range from 4 to 25 kDa and 20 to 250 kDa, respectively, accumulating 900 shots per spectrum.…”
Section: Maldi-tof Ms Profiling Of Serum Proteinsmentioning
confidence: 99%
“…Sample preparation of peptide mixtures was performed on an AnchorChip 600/384 target plate [32] using CHCA as matrix. Peptide mixtures were analyzed with a Reflex III MALDI TOF mass spectrometer (Bruker Daltonik) equipped with the SCOUT source and delayed extraction and operated in positive ion mode using an acceleration voltage of 20 kV [25]. Spectra were externally calibrated using a commercially available Peptide Calibration Standard (Bruker Daltonik) as well as internally recalibrated using the following peptide ion signals derived from trypsin autoproteolysis: …”
Section: Mass Spectrometric Peptide Mass Fingerprintingmentioning
confidence: 99%
“…Humans express three different forms of Hp a-subunits, a1S, a1F and a2, that combine with a single b-subunit to generate multimers (Bowman & Kurosky, 1982;Mikkat et al, 2004;Tubbs et al, 2005). Pigs possess one a-subunit, which resembles human Hp-a1S, with one b-subunit (Ponsuksili et al, 2002).…”
Section: Discussionmentioning
confidence: 99%